Radiation-induced polymerization of 3-hexylthiophene in oxygen-free and oxygen-saturated dichloromethane solvent. (March 2021) - Bahry, Teseer; Cui, Zhenpeng; Dazzi, Alexandre; Gervais, Matthieu; Sollogoub, Cyrille; Goubard, Fabrice; Bui, Thanh-Tuân; Remita, Samy
Abstract: As alternative radiolytic approach, the synthesis of P3HT was made possible thanks to the oxidation of 3HT monomers by chloromethyl and dichloromethyl radicals or by their corresponding peroxyl radicals in situ produced by dichloromethane solvent radiolysis. Under two different experimental conditions, in oxygen-free solution and in oxygen-saturated solution, two different polymers, " P 3 H T N 2 " and " P 3 H T O 2 " respectively, were successfully synthesized. Both produced materials were discerned by several analytical and spectroscopic techniques. UV–Vis absorption spectroscopy results showed that the radiolytic yield of 3HT oxidation in dichloromethane solvent is higher under O2 atmosphere. Indeed, a dose of 75 kGy was needed to polymerize 10 mM in 3HT under N2 atmosphere, meanwhile a dose of 35 kGy was sufficient to polymerize the same amount of 3HT under O2 . The average molecular weight of P 3 H T O 2 was found higher than that of P 3 H T N 2 as revealed by SEC chromatography analysis. Also, P 3 H T O 2 exhibits better thermal stability than P 3 H T N 2 . ATR-FTIR spectroscopy revealed the specific presence into P 3 H T O 2 polymers of some functional groups such as carbonyl, hydroxyl and carboxyl moieties, which clearly explains the difference between the morphological structures of P 3 H T N 2 and P 3 H T O 2 as highlighted by cryo-TEM, SEM and AFM microscopies. Finally, both radio-synthesized P 3 H T N 2 and P 3 H T O 2 polymers were found characterized by remarkably significant conductive, electronic and optical properties. Graphical abstract: Image 1 Highlights: Radiolysis is successfully used for the synthesis of P3HT polymers in DCM solvent. Doped conducting P3HT polymers are produced either under O2 or under N2 atmospheres. Functionalization and morphology are found different according to the atmosphere. Working under O2 improves polymerization efficiency and increases molecular weight. O2 atmosphere enhances thermal stability and increases electrical conductivity.